The Pierrot ensembles: Chronicle and catalogue, 1912-2012 - Dromey, Christopher; Wintle, Christopher (London Plumbago Books, 2012)
Christopher Dromeys illuminating study manages a distinctive and well-researched account of how composers have received Schoenbergs Pierrot lunaire by focussing on a selection of different, and mainly British, historical and institutional contexts. By gearing the text to the illustrations, it should give readers a good understanding of why one relatively small-scale early twentieth-century composition has had such a lasting impact.Arnold Whittall (Kings College London)2012 is the centenary of the first performance of Arnold Schoenbergs Pierrot lunaire, Op. 21, and over the last hundred years its mixed chamber ensemble has become, in all its protean forms, a principal line-up for modern music. This book, the first of its kind, chronicles the ensembles evolution from Pierrots earliest performances, monitoring its influence on the Continent as well as upon Walton, Britten, Lutyens and Searle in Britain. In particular, it watches the growth of The Pierrot Players (later The Fires of London), one of the most galvanizing groups in post-war British music, and looks carefully at the social dynamics among its players and composers, notably Peter Maxwell Davies and Harrison Birtwistle. The influence of Pierrot, however, has not been confined to Europe and Britain. In the final section the author catalogues over 400 principal works for Pierrot Ensembles with or without singer drawn from both sides of the Atlantic. An appendix includes the first reprinting of Stephen Pruslins text for Birtwistles controversial Monodrama (1967). The book is richly illustrated with photographs, drawings, music examples and diagrams.CHRISTOPHER DROMEY took his PhD at Kings College London and is now Senior Lecturer in Music at Middlesex University. In addition to theory and analysis, he teaches musicology and copyright law, and has published on Benjamin Britten (British Music and Modernism, 1895-1960, Ashgate, 2010), Alexander Zemlinsky (Zemlinsky Studies, Middlesex UP, 2008) and Peter Maxwell Davies (New Makers of Modern Culture, Routledge, 2007).CHRISTOPHER WINTLE (Editor) is a Senior Research Fellow in Music at Kings College London and Director of The Hans Keller Archive. His many publications include a monograph on Benjamin Britten, All the Gods (Plumbago, 2006), Metapoetics (Plumbago, 2010), and a study of the rehearsal scores for Brittens Death in Venice (in Rethinking Britten, OUP, 2013).